Teachers’ Job Commitment and Its Relationship with School Effectiveness in Public Secondary Schools in Kwara State, Nigeria - Oba Baba Ayoku; Bashiru Ibrahim Ajadi; Adeseko Sunday Olaifa; Yusuf Olatunji Onimago; Tejidini Lateef Ahmed; Abdullahi Yakub (Universitas Islam Bunga Bangsa Cirebon, 2025)
Education remains a vital instrument for social and economic transformation, yet the quality of secondary education in Nigeria continues to face challenges linked to teachers’ low morale and limited institutional support. Teachers’ job commitment—reflected in promotion satisfaction, job security, and working conditions plays a central role in determining how effectively schools achieve their goals. This study examined the relationship between teachers’ job commitment and school effectiveness in public senior secondary schools in Kwara State, Nigeria. A descriptive correlational survey design was employed, involving 313 respondents (268 teachers and 45 principals) selected through multi-stage sampling. Data were collected using a validated questionnaire titled Teachers’ Job Commitment and School Effectiveness Questionnaire (TJCSEQ), and analysed with descriptive statistics and the Pearson Product-Moment Correlation (PPMC) at the 0.05 significance level. Findings revealed that both teachers’ job commitment and school effectiveness were at moderate levels. Significant positive relationships were found between teachers’ promotion and school effectiveness (r = 0.54, p < 0.05), job security and school effectiveness (r = 0.16, p < 0.05), and working conditions and school effectiveness (r = 0.30, p < 0.05). These results indicate that fair promotion, stable employment, and supportive environments enhance teachers’ dedication and contribute to more effective schools. The study concludes that improving teacher welfare and institutional management practices is critical for achieving sustainable school effectiveness. It contributes empirical evidence from North-Central Nigeria and offers a framework for policymakers to strengthen teacher motivation and educational quality nationwide.